Experimental methods for the mechanical characterization of cycling short pads - Marcolin, G.; Panizzolo, F. A.; Paoli, A.; Petrone, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
In cycling, non-traumatic injuries affecting the genitourinary tract have been the most extensively studied considering their effect in reducing the quality of life. The employment of saddle with specific geometries and of cycling shorts with pads can contribute to reduce the pressure on the perineal area and to increase the level of comfort. The aim of this study was to develop a method to quantify the mechanical properties of pads which can influence the cyclist`s perineal protection and its level of comfort. The proposed method consisted of both a laboratory and a field test component. The laboratory part included an accelerated fatigue test of 300,000 cycles performed with an hydraulic actuator. Loads employed were derived from pressure data collected on the saddle of a professional cyclist who pedalled both on asphalt and crossing potholes at a constant speed. The measurement of cylinder force and displacement allowed to calculate the damping and the stiffness over time for the pads tested. The field test allowed to collect the acceleration at the seatpost of the bike and at the back of the cyclist by means of two accelerometers. A transfer function (H(f)) allowed to quantify the vibration transmissibility of the pads. The application of our method characterized the pads tested concerning damping, stiffness and vibration transmissibility. This method could be useful for the manufacturer in the choice of density and thickness of foams, to obtain the desired level of protection, comfort and long-time efficacy of pads.